Research hotspots and trends on neuropathic pain-related mood disorders: a bibliometric analysis from 2003 to 2023 - Wang, Xiaohua; Zhuang, Yueyang; Lin, Zhigang; Chen, Shuijin; Chen, Lechun; Huang, Hongye; Lin, Hui; Wu, Shiye (Frontiers in Pain Research, 2023)
Introduction Neuropathic Pain (NP) is often accompanied by mood disorders, which seriously affect the quality of life of patients. This study aimed to analyze the hotspots and trends in NP-related mood disorder research using bibliometric methods and to provide valuable predictions for future research in this field. Methods Articles and review articles on NP-related mood disorders published from January 2003 to May 2023 were retrieved from the Web of Science Core Collection. We used CiteSpace to analyze publications, countries, institutions, authors, cited authors, journals, cited journals, references, cited references, and keywords. We also analyzed collaborative network maps and co-occurrence network maps. Results A total of 4,540 studies were collected for analysis. The number of publications concerning NP-related mood disorders every year shows an upward trend. The United States was a major contributor in this field. The University of Toronto was the most productive core institution. C GHELARDINI was the most prolific author, and RH DWORKIN was the most frequently cited author. PAIN was identified as the journal with the highest productivity and citation rate. The current research hotspots mainly included quality of life, efficacy, double-blind methodology, gabapentin, pregabalin, postherpetic neuralgia, and central sensitization. The frontiers in research mainly focused on the mechanisms associated with microglia activation, oxidative stress, neuroinflammation, and NP-related mood disorders. Discussion In conclusion, the present study provided insight into the current state and trends in NP-related mood disorder research over the past 20 years. Consequently, researchers will be able to identify new perspectives on potential collaborators and cooperative institutions, hot topics, and research frontiers in this field.